ANALISIS KEWAJIBAN PERPAJAKAN BADAN USAHA MILIK DESA DALAM KEBANGKITAN EKONOMI PASCAPANDEMI COVID-19 - Iwan Ramdhanny; Aniek Juliarini (Polytechnic of State Finance STAN, 2022)
This study aims to describe the taxation aspects of Village-Owned Enterprises (BUMDes) in accordance with applicable laws and regulations. The type of research is normative juridical using literature review and applicable tax provisions. The data are taken from the Tax Knowledge Base, pajak.go.id, Jaringan Dokumentasi dan Informasi Hukum, and Google Scholar data. The research method is descriptive qualitative by recording, studying, analyzing, interpreting, and explaining descriptively the object of research. The results of the data analysis show that, in practice, BUMDes tax obligations are the same as corporate tax obligations in general. BUMDes' tax obligations begin by registering its business and/or being confirmed as a Pengusaha Kena Pajak, withholding or collecting taxes, depositing and reporting obligations, and corporate income tax obligations. This study concludes that there are no provisions that specifically regulate the tax obligations of BUMDes. A good understanding of tax obligations, it is hoped it will advance in improving the economy and managing village potential as taxpayers. Government is expected to issue more specific regula-tions regarding tax obligations related to BUMDes. For the next research, it can take some field data.